Flood impact on the transport, transition, and accumulation of phosphorus in a reservoir: A case study of the Biliuhe Reservoir of Northeast China. (1st January 2021) - Yu, Huijuan; Xu, Shiguo; Tian, Wen; Zhu, Tongxin; Chen, Xiaoqiang
Abstract: Stormflow runoff is the most important agent for phosphorus (P) input to reservoirs, as the particulates contained in runoff carry a substantial amount of P. The settling process of particulates affects the P content of water, and the distribution of particulates determines the P distribution in reservoir sediment. An understanding of flood impacts on the transport, transition, and accumulation of P in a reservoir is critical to reservoir management. In this study, water samples before and after flooding and sediment samples after flooding were collected from Biliuhe Reservoir in Northeast China. P content and load in the water and P-fractions and particle sizes of the sediments were analyzed. Results showed that total particulate P (TPP) increased sharply from 1.56 to 26.72 t after flooding, whereas dissolved organic P (DOP) decreased markedly from 3.24 to 1.17 t, which was largely caused by biological uptake directly or indirectly before flooding. Orthophosphate ( PO 4 3 − ) shared a similar trend with TPP, indicating that PO 4 3 − could be adsorbed onto settling particulates, helping to reduce the reactive P introduced by flooding. Reservoir sediment showed a fining trend downstream and the clay fraction exhibited an obvious correlation with P-fractions, demonstrating that the distribution of particulate matter determined P distribution in the sediment. This study also found that particulates from the largest tributary (Biliu River) were only minimally transported from its reservoir entrance to the dam because of a longer travel distance, while contrastingly, particulates from a smaller tributary (Bajia River) were maximally carried to the dam because of a shorter distance. Our fundings suggests that surface water in the reservoir should be released prior to flooding in order to mitigate control of P in the water, moreover, it is necessary to strengthen the effectiveness of pollutant control projects at the reservoir entrance of the Bajia River. Graphical abstract: Image 1 Highlights: Biological uptake before flood may reduce dissolved organic phosphorus (P) load. Particulate has slow adsorption of PO 4 3 − during settling. Abundant iron source in basin is crucial to keep low P content in reservoir water. The distribution of particulate determined the distribution of P in sediment. Surface water should be released prior to flood for P control in reservoir. Abstract : The slow adsorption of P O 4 3 − by particulates during settling has an effect on decreasing the reactive P load. The discharge of water with particulates during the flood season may result in higher retention of reactive P in water.